Age Related Morphological Studies on the Tongue of Non-Descript Sheep of Jammu Region with Special Emphasis on Lingual Papillae - Sethi, Lovish; Sarma, Kamal; Suri, Shalini; Devi, Jonali; Singh Sasan, Jasvinder; Chakraborty, Dibyendu (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The tongue of the non-descript sheep (n = 18) was a spatula shaped mobile organ consisting of apex, body, and root. The apex was  notched at the centre. A longitudinal groove on the dorsal surface was present which was more apparent in the adult and senile groups.  Caudo-dorsal portion of the body presented torus linguae, in front of which was a transverse fossa linguae. Dorsal surface of the tongue  was covered by filiform, fungiform, conical, lenticular, and circumvallate papillae. Filiform papillae were pointed, thread-like, and directed  caudally and were most abundant. Fungiform papillae were mushroom-shaped. Filiform and fungiform papillae were also present on the  ventral surface of the tongue tip in ‘V’ configuration in all three age groups (below 1 year; 2-3 years,and 4 years and above). Lenticular  papillae were found on the torus linguae. Largest lenticular papillae were placed along the midline of the prominence. Conical papillae  were found lateral to lenticular papillae and orientated caudally. They were greater in the centre and smaller towards the caudal and  lateral aspects. Circumvallate papillae were spherical and encircled by a deep moat which was surrounded by a slightly higher mucosal  ring. They were arranged in two rows. Weight and volume of the tongue was significantly (p
Keywords: Gross anatomy; Lingual papillae; Sheep; Tongue; Torus linguae